Socialization of the population in the modern regional development of Belarus: the information aspect - Korshuk, Viktoryia V. (Journal of the Belarusian State University. Journalism, 2019)
The need to study socialization as one of the priority directions of the mass media on the implementation of the regional development policy in Belarus is being updated: the argumentation of strengthening ideological work on the part of the mass media with the inhabitants of regions, proposals is worked out for optimizing the activity of the mass media in the process of effective socialization of the rural population, the mechanism of this activity is considered on the example of the work of «Sel’skaya gazeta» – the office of the «Publishing house “Belarus Segodnya”».